Kualitas Rendang Daging Dengan Metode Pengolahan Yang Berbeda - Afdal Akbar; Wiwik Gusnita (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
Rendang is a traditional food, all regions have a characteristic in making this rendang. The distinctive features found are the ingredients, tools, spices and main ingredients used in each region. The method of processing rendang is one of the characteristics that is found to be different in an area. The method of processing rendang is found specifically in the treatment of spices and meat. This type of experimental research with three repetitions, primary data sourced from 5 limited panelists who filled out an organoleptic questionnaire. The independent variable is rendang with stir-frying and steawing methods then the dependent variable is the quality of the rendang. The data obtained were tabulated into tabular form and analyzed using the statistical T test (t test). The results showed the average value of the effect of processing methods on the bran color was 3.27 and 3.87. No significant effect on the quality of forms 3,13 and 3,20; bran color in 3.20 and 3.67; aromas 3,53 and 3,73; meat texture 3.47 and 3.80; bran texture 3,80 and 3,33; bran flavor 3,87 and 3,80; and the taste of meat 3,53 and 3,73.Keyword: Method of processing, Rendang, Quality